MENYOROTI FENOMENA KDRT PADA KELUARGA-KELUARGA DI PAROKI SPIRITU SANTO MISIR DALAM TERANG EFESUS 5:22-33 - Tamelab, Petrus (Pastoralia Jurnal Penelitian Dosen, 2020)
Generally  violence  means  as  physical  and  psychology  attack  and  also  someone  mental integrity. The violence type concerned in family such as physical, psychological, sexual and economy. The violence concerned at family triggered or caused of many factor and reason such as jealous, envy, low economy, low education and forced marriage. In general, every Christian family member ever concern violence in their family in different way. That conclusion obtained through Descriptive naturalistic method. The writer interview the catholic family in Misir Parish appropriate with the research location which definite to support the Thesis that study on this main research. Based on this situation, church present as a lighter through pastoral agent in creation, catechism, family pastoral and marriage preparation courses. Sint Paul read the context in His era mandate Christ love become base of the husband and wife in the same manner as intended on Ephesians 5: 22-33. Although Paul remark became a sign or base for from a new catholic family. That love must always alive on a true catholic family